PENGAJARAN BIPA MELALUI VIDEO ANIMASI CERITA RAKYAT INDONESIA DI SEKOLAH CANBERRA AUSTRALIA - Liliana Muliastuti; Iqbal Ifada (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
In accordance with the mandate of Article 44 Paragraph (1) of Law Number 24 of 2009, the Indonesian government successfully proposed the Indonesian language as an official language at a UNESCO session. This proposal was unanimously accepted during the UNESCO General Assembly on November 20, 2023, making Indonesian one of the ten official languages used in the session. This designation enhances Indonesia's image on the global stage as a nation that supports cultural diversity and is committed to promoting these values internationally. However, in Australia, the teaching of Indonesian as a foreign language (BIPA) has seen a decline over the past two decades. To revive interest in learning Indonesian, the Faculty of Languages and Arts at Universitas Negeri Jakarta (FBS-UNJ), through its Master of Indonesian Language Education Program, introduced Indonesian folklore through animated videos to students at two schools—Trinity Christian School and Burgmann Anglican School—in February 2024. The evaluations from both schools indicated that teaching BIPA through animated folklore videos is a highly effective means of promoting Indonesian language and culture. They expressed hope that similar programs could be continued and expanded with internship opportunities and joint research initiatives. Keywords: bipa teaching; folktales; animated video   Abstrak Pemerintah Indonesia, sesuai dengan amanat Pasal 44 Ayat (1) Undang-Undang Nomor 24 Tahun 2009, telah berhasil mengajukan bahasa Indonesia sebagai bahasa resmi dalam sidang UNESCO. Usulan ini diterima secara bulat pada Sidang Umum UNESCO tanggal 20 November 2023, menjadikan bahasa Indonesia salah satu dari sepuluh bahasa resmi yang digunakan dalam sidang tersebut. Penetapan ini memperkuat citra Indonesia di mata dunia sebagai negara yang mendukung keragaman budaya dan berkomitmen mempromosikan nilai-nilai tersebut di tingkat global. Namun, di Australia, pembelajaran bahasa Indonesia bagi penutur asing (BIPA) telah mengalami penurunan selama dua dekade terakhir. Untuk menghidupkan kembali minat belajar bahasa Indonesia, Fakultas Bahasa dan Seni Universitas Negeri Jakarta (FBS-UNJ) melalui Program Studi Magister Pendidikan Bahasa Indonesia, melaksanakan kegiatan pengenalan cerita rakyat Indonesia melalui video animasi kepada siswa di dua sekolah, yaitu Trinity Christian School dan Burgmann Anglican School pada Februari 2024. Berdasarkan hasil evaluasi oleh kedua sekolah bahwa pengajaran BIPA melalui video animasi cerita rakyat sebagai sarana mempromosikan bahasa dan budaya Indonesia sangat efektif dan berharap agar program serupa dapat dilanjutkan dan diperluas dengan program magang serta penelitian bersama. Kata Kunci: pembelajaran bipa; cerita rakyat; video animasi